In vitro Plant Regeneration of Withania somnifera - Supe, Ujjwala; Dhote, Fanisha; Roymon, MG (Plant Tissue Culture and Biotechnology, 2008)
Key words: Seed explants, Withania somnifera, Micropropagation DOI = 10.3329/ptcb.v16i2.1112 Plant Tissue Cult. & Biotech. 16(2): 111-115, 2006 (December)